2016
DOI: 10.1002/sec.1762
|View full text |Cite
|
Sign up to set email alerts
|

A generalised wavelet packet‐based anonymisation approach for ECG security application

Abstract: An electrocardiogram (ECG) signal contains cardiovascular information, which is private in nature. Therefore, during the distribution and storage of an ECG in a public repository, it is necessary to anonymise the ECG data. An eavesdropper could record an unsecured ECG and use it as recognition data to gain access via an ECG biometric system. Anonymised ECG data also hide cardiovascular details of a patient upholding Health Information Protection and Privacy Act (1996) regulations. In this paper, a generalised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…A study by way of computer simulation in [26] showed that replacing the wavelet decomposition and reconstruction procedures using the fast Fourier transform (FFT) method could achieve the speed of processing 5 times faster than the waveletpacket based algorithm. For example, this study showed that the proposed method could anonymize ECG data with a length of 16,384 points in 3 ms only, while in contrast to that, the wavelet-packet transform as in [29] required approximately 33 ms to complete the whole anonymization process using the same evaluated ECG data. Therefore, the proposed ECG security method in [26] could be considered as the most suitable algorithm (compared to the existing ones) for implementation of the whole set of systems in the IoT environment, where some constraints like power and computation limitations could be substantial factors.…”
Section: A Review On Anonymization Methodsmentioning
confidence: 92%
See 3 more Smart Citations
“…A study by way of computer simulation in [26] showed that replacing the wavelet decomposition and reconstruction procedures using the fast Fourier transform (FFT) method could achieve the speed of processing 5 times faster than the waveletpacket based algorithm. For example, this study showed that the proposed method could anonymize ECG data with a length of 16,384 points in 3 ms only, while in contrast to that, the wavelet-packet transform as in [29] required approximately 33 ms to complete the whole anonymization process using the same evaluated ECG data. Therefore, the proposed ECG security method in [26] could be considered as the most suitable algorithm (compared to the existing ones) for implementation of the whole set of systems in the IoT environment, where some constraints like power and computation limitations could be substantial factors.…”
Section: A Review On Anonymization Methodsmentioning
confidence: 92%
“…Finally, the original ECG was recovered by combining the secret key and the distorted ECG data on the receiver side using the reconstruction method. Careful examination in [29] showed that the method in [28] does not fully conceal the fiducial features of the ECG. The reason is that the RRinterval is still present in the anonymized ECG data and can still be identified easily; consequently, heart rate variability of a patient can be revealed using this anonymized data.…”
Section: A Review On Anonymization Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dalam laporan penelitian tersebut dijelaskan bahwa proses pengamanan sinyal EKG dapat diterapkan pada perangkat genggam. Model lain yang diusulkan dalam pengamanan sinyal EKG adalah dengan menggunakan proses anonimasi sinyal EKG (Mahmmoud, 2016). Dalam paper ini, proses anonimasi dilakukan dengan bantuan waveletpacket, yaitu dengan melakukan modifikasi terhadap sub-band frekuensi rendah setelah proses dekomposisi sinyal EKG oleh algoritma wavelet-packet.…”
Section: Pendahuluanunclassified